Bargibant’s pygmy seahorse Hippocampus bargibanti in Taiwan Bank: hidden biodiversity of Taiwan Strait - Jiang, Guo-Chen; Chen, Kuo-Shu; Chen, Yi-Hsuan; Weng, Jinn-Shing; Yeh, Hsin-Ming; Shen, Kang-Ning; Chang, Chih-Wei (Zootaxa, 2024)
During a scientific expedition in the Taiwan Bank in the southern Taiwan Strait in 2021, five pygmy seahorses, measuring between 18.1 mm and 28.3 mm in standard length, were inadvertently collected along with Muricella sea fans. Morphometric measurements of these pygmy seahorse specimens coincided with the previous data on H. bargibanti, but they had a proportionally greater head depth and snout length. Genetically, DNA marker analysis of partial mitochondrial COI sequences confirmed that our specimens belonged to the same lineage as H. bargibanti, with a p-distance of 0.54% among populations. This discovery enhances our knowledge of the limited biodiversity in the Taiwan Bank, which includes a complex geomorphology of both reef banks and sandy substrates, and highlights the importance of strict laws prohibiting fishing with inadequate gear, invasive or illegal fishing, and sand dredging to protect unexplored coral reef biodiversity in the area.